Synthesis and structure-activity relationships of ring D alkyl 19-norsteroids - Loedolff, Michiel Christiaan (Department of Chemistry, 2016)
Studies have been conducted in synthesising ring D alkyl 19- norsteroids. The aim was to investigate methods for the stereoselective introduction of alkyl groups at C(14) and C(15), for eventual conversion of the intermediates into 14- and 15-alkyl analogues of estradiol hormones. In the first phase of this investigation, 17β-tert-butyldimethylsilyloxyestra-1,3,5(10),14-tetraen-l6-one was synthesised as starting material for alkylation experiments. Estrone 3-methyl ether was converted into the derived 17β-hydroxy 16-ketone by standard methods. This conversion involved the introduction of a 16α-hydroxyl group by bromination-hydrolysis, followed by base-mediated rearrangement of the hydroxy ketone to the thermodynamically preferred 16-ketone. Protection of the 17β-hydroxyl group as a TBS ether, followed by palladium acetate-mediated dehydrosilylation of the derived ∆¹⁵-16-trimethylsilyloxy enol ether gave the ∆¹⁴-16-ketone.The 17β-silyloxy ∆¹⁴-16-ketone resisted conjugate addition reactions, leading only to products of 1,2-alkylation. Stereoselective introduction of a 16-allyl group gave the corresponding ∆¹⁴-16-allyl 16-alcohols, but these compounds showed no sigmatropic reactivity and failed to undergo anionic oxy-Cope rearrangement. Hydride reduction of the 16-oxo group gave the corresponding At4-16-alcohols. The stereoselectivity was dependant on the choice of reagent. The ∆¹⁴-l6α-alcohol underwent ·stereodirected cyclopropanation to give 17β-tert-butyldimethylsilyloxy-14,15α-methyleneestra-1,3,5(10)-trien-16α-ol. Oxidation of this compound gave the corresponding 14α,15α methylene16-ketone, dissolving metal reduction of which furnished the 16β-alcohol. Routine deprotection of the epimeric pair of methylene 16-alcohols gave the derived estriol analogues, which were subjected to biological evaluation. Treatment of the 14α,15α methylene16-ketone with lithium in liquid ammonia gave 17β-tert-butyldimethylsilyloxy-14-methylestra-l,3,5(10)-trien-16-one. Stereoselective reduction of the 16-oxo group gave the epimeric 14α-methyl 16-alcohols. Deprotection of these compounds at C(3) gave a second pair of estriol analogues, which were also assayed for receptor binding affinity.